Cutaneous Rosai-Dorfmans nodules on cheek - Sundaramoorthy M. Srinivasan; Suganthi Parthasarathy (Our Dermatology Online, 2016)
Sinus histiocytosis with massive lymphadenopathy (SHML) or Rosai-Dorfman disease (RDD) is a benign idiopathic histiocytic proliferative disorder that commonly involves the lymph nodes but secondarily involves the skin. However, purely cutaneous disease without lymphadenopathy or internal organ involvement may rarely occur. We report a patient who presented with asymptomatic non-specific enlarging skin nodules without evidence of lymphadenopathy or internal disease. Histopathological examination of skin lesions in this patient showed proliferation of large histiocytes with phagocytosed inflammatory cells characteristic of Rosai-Dorfman disease. The diagnosis of purely cutaneous Rosai - Dorfman disease may be complicated by its rarity, nonspecific clinical appearance of skin lesions and broad histopathological differential diagnosis of this disorder. The prognosis is excellent in most cases. Complete spontaneous regression is known to occur. Both physicians and pathologists need to be aware of rare conditions which masquerade as lymphoproliferative disorders. Here we describe one such clinical condition - "Cutaneous Rosai Dorfman disease" and an approach to such patients.